Women and Children as Victims of Financial-based Violence in Online Gambling Circles: A Criminological Approach to Criminal Law and Rehabilitation Policy in Indonesia - Kamalludin, Iqbal (Sawwa: Jurnal Studi Gender, 2024)
Online gambling in Indonesia increasingly exposes women and children to financial-based violence, making them vulnerable groups. Despite the rise in online gambling, current legal policies and rehabilitation programs have failed to fully address its harmful social effects. This study analyzes the criminogenic factors that contribute to victimization among women and children and evaluates the effectiveness of criminal law policies and rehabilitation programs in safeguarding them. Through a normative legal research method, utilizing legislative analysis, criminology, and case studies, the findings reveal that existing policies are inadequate and overlook the complexity of financial violence in this context. Rehabilitation programs also tend to be less effective, focusing primarily on legal and therapeutic approaches while neglecting broader social, economic, and cultural influences. This research proposes a more comprehensive and rehabilitative policy framework that not only seeks to punish offenders but also prioritizes prevention, reducing violence recurrence, and enhancing social reintegration for victims.